Constitutional semiotics : the conceptual foundations of a constitutional theory and meta-theory - Belov, Martin (London [England] : Hart Publishing, 2022)
"This book offers an outline of the foundations of a theory of constitutional semiotics. It provides a systematic account of the concept of constitutional semiotics and its role in the representation and signification of meaning in constitution, constitutional law, and constitutionalism. The book explores the constitutional signification of meaning that is stretched between rational entrenchment and constitutional imagination. It provides a critical assessment of the rationalist entrapment of constitutional modernity and justifies the need to turn to 'shadow constitutionalisms': textual, symbolic-imaginary and visual constitutionalism. The book puts forward innovative incentives for constitutional analysis based on constitutional semiotics as a paradigm for representation of meaning in rational, textual, symbolic-imaginary and visual constitutionalism. The book focuses on the textual, imaginative, and visual discourse of constitutionalism, which is built upon collective constitutional imaginaries and on the peculiar normativity of constitutional geometry and constitutional mythology as borderline phenomena entrenched in rational, textual, symbolic-imaginary and visual constitutionalism. The book analyses concepts such as: constitutional text and texture, authoritative constitutional narratives and authoritative constitutional narrators, constitutional semiotic community, constitutional utopia, constitutional taboo, normative ideology and normative ideas, constitutional myth and mythology, constitutional symbolism, constitutional code and constitutional geometric form. It explores the textual entrenchment of constitutionalism and its repercussions for representation and signification of meaning."--
Introduction -- Part I: Constitutional Signification of Meaning: Between Rational Entrenchment, Signification Potential and Constitutional Imagination -- 1. Constitutional Semiotics as a System of Theories and Meta-Theories -- 2. Quantum Constitutionalism as a Trigger of Paradigmatic Turn and the Role of Constitutional Semiotics for Its Proper Understanding -- 3. The Rationalist Entrapment of Constitutional Modernity -- 4. The Concept of Rational Constitutionalism and the Need to Turn to 'Shadow Constitutionalisms' on the Basis of Semiotic Approach -- 5. The Structure of Constitutional Semiotics: Signifiers, Signigfieds and Signification of Constitutional and Constitutionally Relevant Meaning -- Part II: Textual Constitutionalism and Its Role for Constitutional Semiotics -- 1. The Concept of Textual Constitutionalism -- 2. Constitutional Communication Perceived Through the Semiotic Perspective of Textual Constitutionalism -- 3. The Constitution As Discursive Semiotic Project: Constitutional Narratives, Constitutional Narrators and Constitutional Semiotic Community -- 4. Constitutional Text and Constitutional Texture From Semiotic Perspective. The Role of Open Texture for Constitutional Semiotics -- 5. The Concept of Authoritative Constitutional Text and Its Functions for Constitutional Semiotics -- Part III: Symbolic-Imaginary Constitutionalism -- 1. The Concept of Symbolic-Imaginary Constitutionalism -- 2. Constitutional Semiosis via Symbolic-Imaginary Constitutionalism on the Edge Between the Collective Conscious, Subconscious and Unconscious -- 3. Constitutional Semiotic Landscapes: Teleology and Functionality of Symbolic-Imaginary Constitutionalism As 'Game of Constitutional Semiotic Imaginaries' -- 4. Constitutional Codes -- 5. Normative Ideologies and Normative Ideas -- 6. Constitutional Myths and Mythologies -- 7. Constitutional Utopias -- Part IV: Visual Constitutionalism -- 1. Visual Constitutionalism As Post-modern Semiotic Concept -- 2. Official Visual Constitutional Semiotics: The Constitutional Embeddedness and Constitutional Relevance of Official Public Visuals -- 3. Visual Constitutionalism and Digital Constitutional Semiotics: 'Iconisation', 'Emojification', 'Memefication' As Forms of Signification of Constitutionally Relevant Meaning -- 4. Visual Constitutionalism As Proper Form of Constitutionalism Embedded in Semiotic and Socio-Legal Approaches -- 5. Visual Constitutionalism in Pop Culture and Pop Art -- 6. Visual Constitutionalism in Architecture -- Part V: Constitutional Geometry and Constitutional Algebra As Semiotic Paradigms for Ordering and Explaining the Constitution, Constitutionalism and Constitutional Law -- 1. Ordering and Explaining Constitutional Order Through Mathematic Metaphors: An Introduction to the Semiotic Theory of Constitutional Geometry and Constitutional Algebra -- 2. Inspiration, Imagination and Signification Through Rationalization: The Concept of Constitutional Algebra -- 3. The Concept of Constitutional Geometry: Imagining, Signifying, Understanding and Ordering the Constitutional Order Through Geometric Metaphors -- 4. The Semiotic Role of Structured Constitutional Imaginaries -- 5. Constitutional Geometry As Explanatory and Ordering Paradigm of Constitutionalism -- 6. Theoretical Constitutional Geometry -- 7. Imaginative Constitutional Geometry and the Concept of Cloud Constitutionalism -- 8. Westphalian, Post-Westphalian and Neo-Westphalian Constitutional Geometry -- Bibliography -- Index
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Constitutional history; Constitutional law; Electronic books